Diabetes Mellitus Accelerates Alzheimer′s Disease Development by Affecting the Gut Microbiome. - He, Qiong; Zhao, Zixiao; Jiang, Donglang; Fei, Aihua; Abhimanyu, Abhimanyu (BioMed Research International, 2026)
Increasing evidence suggests a link between Alzheimer′s disease (AD) and diabetes mellitus (DM). However, the precise mechanisms by which DM contributes to AD remain unclear. This study is aimed at elucidating the potential role of DM in the early stages of AD. Accordingly, a streptozotocin (STZ)‐induced diabetic 5 × familial AD (FAD) mouse model was established. Immunohistochemistry and positron emission tomography/computed tomography (PET/CT) scanning were performed to examine amyloid beta (Aβ) deposition in the brain. The integrity of the colonic epithelium was assessed using quantitative reverse transcription–polymerase chain reaction (qRT‐PCR) and immunofluorescence staining. Microbial diversity analysis was conducted for 5 × FAD mice with and without STZ‐induced DM to determine shifts in intestinal flora profiles. After oral administration of butyrate to STZ‐treated 5 × FAD mice, we observed that Aβ deposition in the brain was decreased, and the intestinal flora improved. Immunohistochemistry and PET/CT findings revealed a marked increase in Aβ formation in the brains of 5 × FAD mice treated with STZ. qRT‐PCR and immunofluorescence staining revealed severe intestinal barrier dysfunction in these mice. Gut microbiota sequencing indicated significant dysbiosis in STZ‐treated 5 × FAD mice, characterized by a reduction in short‐chain fatty acid (SCFA)–producing species. After oral administration of butyrate, Aβ deposition in the brains of STZ‐treated 5 × FAD mice was significantly reduced, and beneficial changes occurred in the intestinal flora, including increases in bacteria associated with SCFA production and neurological function. Dysregulation of the gut microbiome may exacerbate cerebral amyloidosis during AD pathogenesis. Microbes associated with SCFA production may play a beneficial role in AD treatment, and butyrate supplementation can significantly delay AD progression.